Prevalence of primary osteoporosis and low bone mass in postmenopausal women and related risk factors - Elnaz Hemmati; Mojgan Mirghafourvand; Majid Mobasseri; Seyed Kazem Shakouri; Parvaneh Mikaeli; Azizeh Farshbaf-Khalili (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Globally, 30% of female over 50 years old have osteoporosis. This disease is one of the major causes of disability and death in the elderly. This research was aimed to determine the prevalence of primary osteoporosis and low bone density based on bone mineral density in postmenopausal women and its sociodemographic, obstetric, and life style risk factors. MATERIALS AND METHODS: This cross-sectional descriptive-analytical study was performed by simple random sampling on 850 postmenopausal women aged 50-65 years covered by all health centers, from August 2018 to April 2019, in Tabriz-Iran. Four hundred and forty-five eligible women underwent densitometry using dual-energy X-ray absorptiometry in the lumbar spine and femoral neck. Socio-individual, obstetric-medical, international physical activity questionnaires-short form, and anthropometric questionnaires were completed. Data analyzed using descriptive and analytical statistics including multivariate logistic regression in SPSS 21 software. RESULTS: The prevalence of primary osteoporosis based on lumbar vertebra T-score, femoral neck T-score, and total was 23.4%, 3.4%, and 24.5%, respectively, and the prevalence of primary osteopenia based on lumbar vertebra T-score, femur neck T-score, and total was 42%, 35.5%, and 43.6%, respectively. The present study showed that the odds of osteoporosis increased by increment of age (odds ratio [OR]: 1.18; 95% confidence interval [CI]: 1.07-1.30), but it decreased by increasing menopausal age (OR: 0.92; 95% CI: 0.85-1.01), body mass index (OR: 0.87; 95% CI: 0.78-0.97), arm circumference (OR: 0.84; 95% CI: 0.74-0.95), and education level (P = 0.028). It was higher in unmarried women (OR: 2.65; 95% CI: 0.99-7.08) and those with nonpersonal housing (OR: 4.02; 95% CI: 1.24-13.07). CONCLUSIONS: Given the high prevalence of primary osteoporosis and low bone mass in postmenopausal women, health education is necessary for preventing modifiable risk factors and reducing the complications of this disease.